2012
DOI: 10.1103/physrevc.85.025801
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the neutron starr-mode instability window to the density dependence of the nuclear symmetry energy

Abstract: Using a simple model of a neutron star with a perfectly rigid crust constructed with a set of crust and core equations of state that span the range of nuclear experimental uncertainty in the symmetry energy, we calculate the instability window for the onset of the Chandrasekhar-Friedmann-Schutz (CFS) instability in r-mode oscillations for canonical neutron stars (1.4M⊙) and massive neutron stars (2.0M⊙). In these models the crust-core transition density, and thus crustal thickness, is calculated consistently w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
64
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 52 publications
10
64
7
Order By: Relevance
“…A similar study has been recently done by Wen, Newton and Li in Ref. [45] using a simple model for the EoS that consistently describes the crust-core transition density. Assuming that the main dissipation mechanism of the r-modes is due to the electron-electron scattering at the crust-core boundary, and using the estimated core temperature of several low-mass X-ray binaries (LMXB), these authors conclude that neutron stars are stabilized against r-mode oscillations if L is smaller than ∼ 65 MeV.…”
Section: Introductionmentioning
confidence: 91%
“…A similar study has been recently done by Wen, Newton and Li in Ref. [45] using a simple model for the EoS that consistently describes the crust-core transition density. Assuming that the main dissipation mechanism of the r-modes is due to the electron-electron scattering at the crust-core boundary, and using the estimated core temperature of several low-mass X-ray binaries (LMXB), these authors conclude that neutron stars are stabilized against r-mode oscillations if L is smaller than ∼ 65 MeV.…”
Section: Introductionmentioning
confidence: 91%
“…[4][5][6]. Recently, appreciable progresses have been achieved on constraining the symmetry energy at saturation and subsaturation densities either through the extraction based on astrophysical observations or in terms of terrestrial data [7][8][9][10][11][12]. However, the density dependence of the symmetry energy is still poorly known at supranormal densities [3,[13][14][15].…”
mentioning
confidence: 99%
“…In what follows we will use the same approach as discussed in Ref. [111,112,113,114]. By assuming that the crust of the neutrons star is perfectly rigid, one can find an upper limit on the instability window.…”
Section: The R-mode Instability In Neutron Starsmentioning
confidence: 99%
“…In the realistic case of more elastic crust, the dissipation from the core-crust boundary decreases and therefore widens the instability window. In a recent work involving some of us [111], we studied the sensitivity of the r-mode instability to the density dependence of the symmetry energy. In particular, by employing a simple model of a neutron star with a perfectly rigid crust constructed with a set of crust and core EOS that span the range of nuclear experimental uncertainly in the symmetry energy, we found that EOSs characterized by the density slope L of smaller than 65 MeV are more consistent with the observed frequencies in LMXBs.…”
Section: The R-mode Instability In Neutron Starsmentioning
confidence: 99%
See 1 more Smart Citation